HUBUNGAN ANTARA KUALITAS LAYANAN CUSTOMER SERVICE DENGAN KEPUASAN PELANGGAN - Putri Astiti (JP3M: Jurnal Pendidikan, Pembelajaran dan Pemberdayaan Masyarakat, 2019)
The proposed research study the correlation between five dimension of service quality and customer satisfaction, in which the five dimension include of tangibility, reliability, ability to response, assurance, and empathy. Correlation method and quantitative analysis technique are used in this research. Data and information needed should be accurate and factual to be gathered and arranged systematically, supported by deep observation, literature study, and interview to management of Toserba in Banding City. Therefore, 98 of 5,428 active Toserba Card users on Toserba was taken as sample.The result of this research shows a strong correlation between Service Quality Of Customer Service And Customer Satisfaction Toserba which mean service quality has significant contribution to customer satisfaction on Pasaraya Toserba . The results of this study indicate that Toserba need additional training in order to improve the quality of customer service.